Just like us : the true story of four Mexican girls coming of age in America - Thorpe, Helen, 1965- (New York, NY : Scribner, 2009)
By the time Marisela, Yadira, Clara and Elissafour girls of Mexican descent from the suburbs of Denverentered their freshman year in high school, they were inseparable, but four years later, their fundamental difference threatened to divide them: Clara and Elissa were legal residents, but Marisela and Yadira had begun to suffer the repercussions of their parents' choice to illegally enter the U.S. Journalist Thorpe, married to Denver mayor John Hickenlooper, met them as the girls without legal status were finding their friends' libertiesbig and smallto attend college, drive or even rent a movie unbearable. It was hard for Marisela and Yadira to see why they should labor over their homework if they were just going to end up working at McDonald's, Thorpe writes. Marisela slid into trouble with ease, but Yadira found the experience profoundly disorienting. With striking candor, Thorpe chronicles the girls' lives over four years, delineating the small but arresting differences that will separate them and shape their futures. She personalizes the ongoing debate over immigration and frames it so compassionately and sensibly that even the staunchest opponents of immigration liberalization might find themselves rethinking their positions.
Keywords: Mexican American women -- Colorado -- Denver -- Social conditions; Illegal aliens -- Colorado -- Denver; Denver (Colo.) -- Social conditions; Denver (Colo.) -- Social life and customs